2019
DOI: 10.3233/jad-190487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Modified Tai Chi Program on Older People with Mild Dementia: A Randomized Controlled Trial

Abstract: Background: Tai Chi exercise is a non-pharmacological therapy that has received increased attention in recent years. A Tai Chi program has been specifically modified for older people with cognitive impairments by the research team. Objective: We aim to assess the effects of this Tai Chi program on mild dementia. Methods: Eighty older people with mild dementia were recruited and randomly assigned to a Tai Chi group or a control group. The Tai Chi group practiced the Tai Chi program three times a week for 10 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 42 publications
1
59
0
Order By: Relevance
“…MoCA is a 30-item test to evaluate various domain of cognition like executive function, language, memory, abstraction and orientation. MoCA has been extensively used to assess cognitive impairments in adults in many randomized controlled trials 27,40 . Consistent with previous cross-sectional and cohort studies 3,37 , our study found that Hong chuan Tai Chi practitioners had better global cognitive status than Tai Chi-naïve controls.…”
Section: Chi Group Demonstrated Better Performance In Mini-mental Status Examination Colormentioning
confidence: 99%
“…MoCA is a 30-item test to evaluate various domain of cognition like executive function, language, memory, abstraction and orientation. MoCA has been extensively used to assess cognitive impairments in adults in many randomized controlled trials 27,40 . Consistent with previous cross-sectional and cohort studies 3,37 , our study found that Hong chuan Tai Chi practitioners had better global cognitive status than Tai Chi-naïve controls.…”
Section: Chi Group Demonstrated Better Performance In Mini-mental Status Examination Colormentioning
confidence: 99%
“…e sample size ranged from 36 to 398. e overall sample size was 1,970, including 871 in the experimental groups and 1,099 in the control groups. Among the 19 studies included, 16 focused on MCI elderly and three focused on the elderly with dementia [28,29,31]. Participants ranged in age from 66 to 82 years.…”
Section: Assessment Of Studymentioning
confidence: 99%
“…A Cochrane review analyzed the efficacy of nondrug interventions focusing on cognitive rehabilitation for PSCI, and the results showed that more research evidence is needed [14]. Hyperbaric oxygen therapy and Tai Chi may contribute to cognitive improvements, but have not yet been proven to be effective independent therapies [15,16]. Although there are multiple treatments, there are still few effective treatments for PSCI.…”
Section: Introductionmentioning
confidence: 99%